Post-Pandemic Preparedness For Blended Learning Among University Of Mataram Students - Darmiany, Darmiany; Nyoman Karma, I; Erfan, Muhammad (International Journal of Educational Research & Social Sciences, 2023)
In implementing college courses that utilize blended learning, various challenges have emerged. Internet connectivity is identified as a key issue in online learning, according to research findings. Another study highlights evaluation of learning as a significant challenge for educators in higher education. Preliminary investigations show an increase in student cheating, particularly plagiarism, during online courses. This research aims to assess the readiness of FKIP University of Mataram students for blended learning courses. It is a quantitative study using a descriptive approach, where a learning readiness survey instrument with a scoring system is employed. Data are qualitatively analyzed across five key dimensions. The results indicate that students confidently use various platforms like Ms. Office and online course applications, have strong self-directed learning abilities, good learner control, are self-motivated, and can communicate effectively online. Based on these findings, the study concludes that students at the University of Mataram are well-prepared for blended learning.